Cognitive Style In Relation to Academic Achievement: Exploring the Relationship between Cognitive Style and Academic Achievement (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Inrecent years, research in teaching-learning process has increasingly shiftedits emphasis from predictive studies of success and failure in performance tothe understanding of cognitive processes that underlie the performance.Prediction of success and failure in academic performance could be of secondaryimportance to the insight into the basic cognitive processes that account foreither of these terminal behaviour.